Aquinas: Commentary - MOONEY, T. Brian (Institutional Knowledge at Singapore Management University, 2011)
Generous selections from these four seminal texts on the theory and practice of education have never before appeared together in a single volume. The Introductions that precede the texts provide brief biographical sketches of each author, situating him within his broader historical, cultural and intellectual context. The editors also provide a brief outline of key themes that emerge within the selection as a helpful guide to the reader. The final chapter engages the reflections of the classic authors with contemporary issues and challenges in the philosophy and practice of education.